Comparative energy and environmental analysis of agro-pellet production from orchard woody biomass. (October 2019) - Rajabi Hamedani, Sara; Colantoni, Andrea; Gallucci, Francesco; Salerno, Mariangela; Silvestri, Cristian; Villarini, Mauro
Abstract: Woody biomass has a considerable potential for energy purposes specially after densification processes which convert these materials into solid biofuels with higher energy density. This study focuses on the energy and environmental assessment of pellet production system from vine and olive grove woody biomass. The life cycle assessment (LCA) from grape and olive cultivation up to packed pellet production, ready for delivery to final users was conducted to quantify the eco-profile of agro-pellet production. The results of comparative analysis revealed that pellet production from both biomasses is dominated by cultivation phase. Vine pellet production was more dependent on chemical fertilizers specially potassium sulfate, but olive pellet production was more dependent on copper oxide pesticide. Primary energy use per MJ energy of vine pellet was greater than that of olive pellet (0.6 vs. 0.19). On the other hand, energy return ratio of olive pellet was three times of that of vine pellet (5.22 vs. 1.7). Nevertheless, olive pellet had higher environmental impacts in the forms of human toxicity, freshwater ecotoxicity and marine ecotoxicity. Consequently, sensitivity analysis investigates the impact of variation in input parameters of fertilizers, pesticides, machinery, diesel fuel, transport and pelletizing process on LCA results. Highlights: Production of pellet from vine and olive cultivation. Life cycle assessment (LCA) of cradle-to-grave of pellets production process. Biomass residues considered as co-product and not byproduct. Comparative analysis revealed that pellet production from both biomass is dominated by cultivation phase.